Consumption of Iron Tablets and Hemoglobin Levels of Anemic Pregnant Women: A Meta-Analysis Study - Rani Nurfitra; Demsa Simbolon (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Iron Tablet Suplement (ITS) Consumption is expected to prevent anemia with increased hemoglobin levels. The 2023 Indonesian Health Survey report shows that 27.7% of pregnant women in Indonesia experience anemia which will have an impact on pregnancy and childbirth complications. The study aims to determine the effect of ITS consumption on increasing hemoglobin levels in anemia pregnant women, so that it can prevent complications of pregnancy, childbirth and the birth of stunted babies. This study uses meta-analysis using the random effect model method. Articles accessed from Google Scholar and PubMed databases. The selection of articles used the PICOTS framework, which included the population of pregnant women, ITS consumption interventions, comparison with the control group that did not consume ITS, the outcome of increasing hemoglobin levels, and the research design in the form of a quasi-experimental study. The inclusion criteria are research articles published in 2010–2022, using a quasi-experimental design, full text available, and mean difference data available. The search used the keywords "iron tablet" AND "hemoglobin" OR "anemic pregnant women" and "Fe tablets" OR "hemoglobin" OR "anemia in pregnant women". The selection process is presented in the PRISMA diagram, 10 eligible articles were obtained. Data analysis using Review Manager application 5.4. The forest plot showed that the pooled mean difference was significant (MD = 1.87: 1.29-2.44; p<0.00001; I² = 96%), then it can be concluded that the consumption of Blood Supplement Tablets significantly increases hemoglobin levels in anemia pregnant women by an average of 1.87 g/dl. The plot funnel shows the standard error of the left plot between 0.1-0.3 while the standard error of the right plot is 0.1-2.9 which shows an almost symmetrical distribution of research where the distribution of points is almost balanced between the left and right sides of the centerline, meaning that there is no publication bias. Consumption of Blood Supplement Tablets is effective in increasing hemoglobin levels in anemia pregnant women, it is recommended to ensure the appropriate dose (60 mg of iron per day), increase compliance through community-based education programs, regular mentoring, the use of reminders, and health policies that facilitate access to ITS for pregnant women, accompanied by regular examinations and distribution at health facilities.